Evaluation framework of reusability QoS metrics for Cloud based SaaS: an empirical study - Sethi, Monika; Kumar, Jatender (International Journal of Computer Sciences and Engineering, 2018)
Cloud based software-as-a-service (SaaS) is a new paradigm where services are offered over the internet. The service providers develop and deploy services that consumers can use to build their applications of high quality. As such, consumers can use these services in various applications and in various combinations. The main concern for every consumer is the quality of the service being provided by the service provider. There are number of quality attributes available to assess the quality of service. Some of the attributes are reliability, scalability, availability, reusability and coupling etc. After reviewing number of QoS attributes, we have found that Reusability and coupling of services, is a key QoS attribute to measure the value and Return on Investment (ROI) of the cloud based software service. In this paper we have proposed a reusability framework for cloud based SaaS and constructed their metrics scores. We have also done empirical evaluation on three different cloud based software services to show applicability of our proposed framework.